Perkawinan Lintas Aliran (Sunni-Syi'ah) - Abdul Haris (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2016)
Muslims in the world-including Indonesia are divided into two major groups, namely the Sunnah and Shi'ah. Although, there are common thing unite them as the unity of Muslims, both have some disagreements that hard to be united; such as attitudes towards companions and Prophet’s wives, about Imamah and Wilayah (leadership and authority) of Ali and the Ahlul Bait, temporary marriages, tahrif al-Qur'an, and so on. Most scholars of Sunnah regard that Shi’ah as heretical / Ahlul Bid'ah, on the other hand mostly Shi’ah cleric's followers regard as Mukhalif Sunnah (the aberrant, violates the truth). As a result, it is not uncommon to open conflict between the followers of the Sunnah (Sunni) and the followers of Shi'ah (Shi'i), even to cause murdering. However, in some areas, cross breeding takes place, between a Sunni and a Shi'i, such as in Bangil Pasuruan, East Java. This study aims to explore the views of religious leaders, both Sunni and Shi'i, in Bangil, on the issue of cross-flow marriage (Sunni-Shi'i). The results showed that in dealing with cross-flow marriage (Sunni-Shi'i), Sunni in Bangil divided into three groups: (1) Conservative; prohibit absolutely. (2) Moderate; does not prohibit but also do not advocate. (3) Liberal; allow it absolutely. While Shi’i leaders agreed to take the attitude of Liberal; allow it absolutely. Marriages cross-flow (Sunni-Shi'i) has the potential to challenge more difficult life than marriage within the flow. The differences in religious rituals, traditions, political views and jurisprudence are prone to trigger psychic conflict. The ordeal is the pressure and rejection of social environment who is not ready to accept the Shi'i community members in the middle of the Sunni, or vice versa